PERBEDAAN KADAR ASAM URAT SEBELUM DAN SESUDAH TERAPI BEKAM - Nabila Permatasari; Bayhakki Bayhakki; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Cupping therapy has been known for a long time and carried out by the community as a treatment to reduce uric acid levels. This study aimed toinvetsigate the value of uric acid levels before and after cupping therapy in Thibbun Nabawi Center RSIA Zainab Pekanbaru. This study design was a cross-sectional design. The sample were 32 respondents taken based on the inclusion criteria using purposive sampling. The measuring tool used was the digital measurement tool for measuring uric acid levels. The analysis used in a univariate analysis to know the frequency distribution and t dependent for bivariate analysis. The result of the study showed that from 32 respondents, 13 respondents (40.6%) were the late adulthood age group, 16 male respondents (50.0%) and 16 female respondents (50.0%), 16 respondents (50.0%) last background education were high school and majority respondents worked as entrepreneurs which is 11 respondents (34.3%) and also 27 respondents (84.4%) have a normal level of uric acid levels before cupping therapy (84.4%). The results of the dependent t test were obtained p value (0.001) <α (0.05), which meant there was a significant difference between before and after cupping therapy for uric acid levels in patients undergoing cupping therapy. Cupping therapy as one treatment can help reduce uric acid levels in the blood so the community can use cupping therapy clinics to reduce uric acid levels. Keywords:Cupping Therapy, Uric Acid Levels